High Performance Work Systems and Public Sector Workplace Performance in Britain - Michael White; Alex Bryson (Institute of Labor Economics (IZA), 2019)
Using nationally representative surveys of workplaces with 50 or more employees we find the adoption of High-Performance Work Systems (HPWS) in the public sector are positively correlated with workplace financial performance and the implementation of workplace organizational change. The associations are stable in 2004 and 2011, despite the intervening recession and cuts in public finance. The results are thus broadly consistent with studies finding similar positive correlations between HPWS and workplace performance in the private sector. There was little heterogeneity in effects across sectors within the public sector, with the exception of health services where the effects of HPWS on workplace change were lower.
Keywords: J45; M5; 330; high performance work systems; public sector; financial performance; organizational change